MAQSaas - Método para avaliação da qualidade em produtos SaaS - Nemesio Freitas Duarte Filho (2011)
The market for software products offered as a service (SaaS) is growing steadily and has attracted vendors from different segments of the global IT market. Many organizations are replacing their conventional software products for SaaS products. But their use has major organizational challenges, cultural and technological. One problem that exists today is the lack of methods and models for assessing the quality of these products. Currently existing models are very generic, not taking specifications relevant to the context of SaaS products. This paper presents a method to assess the quality of a software product offered as a service, called MAQPSaaS. The proposed method has a quality model appropriate to the context SaaS, relying on standards and models of software quality (ISO 9126) and models for IT management (ITIL and COBIT).Your evaluation process includes some steps of ISO 14598, and has some modifications and adjustments by reason of context SaaS. The requirements contained in the model of this approach were mapped on measurable attributes, allowing an assessment of a clear and objective means of checklists. The experimental results (validation and evaluation) show that the method can add efficiency assessment practices for software products offered as services, unable to meet the inefficiencies found in todays valuation